Information authenticity perception of academic librarians on social media for service performance / Nor Zaina Zaharah Mohamad Ariff - Mohamad Ariff, Nor Zaina Zaharah (2022)
Information authenticity can be defined as the truthfulness of the content presented. Social media channels have varieties of information that need to take into account of its authenticity. Issues arise when there are surveys and studies found that librarians lack of skills when facing authenticity issues in social media. This research uses simultaneous quantitative methods through survey questionnaires and descriptive approaches. Public academic libraries in Peninsular Malaysia have been identified from Perangkaan Perpustakaan Akademik 2019, National Library of Malaysia, which reported the total population of the librarians at 520. The optimal sample size of respondents for this study was 225 according to Krejcie and Morgan (1970), with the survey method using questionnaires. From the 450 questionnaires distributed, 349 (97%) of the questionnaires were returned and usable for further analysis. The statistical analyses included descriptive and inferential statistics. Parametric tests were used to analyse the data. For parametric analysis, independent samples t-test, Pearson’s correlation coefficient and multiple regression analyses were used. From the findings, the information authenticity dimensions, familiarity and assurance were found to be the most preferred dimensions as perceived by respondents. Findings revealed that there is a significant relationship between information authenticity dimensions and librarian service performance with a weak to strong degree of correlation. From multiple regression analysis using stepwise method, dimensions on familiarity and assurance were found to be the most significant predictors of librarian service performance. The results indicated that all the six dimensions were moderately correlated with librarian service performance. This implied that the dimensions are required to generate better contribution to the librarian service performance. The outcome of the study is expected to assist the academic libraries and librarian service performance by improving their skills of professionalism and expertise in constructing the authenticity of information by using social media, which will bring many excellent changes in the academic field.